Clinical indicators for severe prognosis of scrub typhus - Pamornsri Sriwongpan (2018)
Background: The study explored clinical risk characteristics that may be used to forecast scrub typhus severity under routine clinical practices. Methods: Retrospective data were collected from patients registered at two university-affiliated tertiary care hospitals in the north of Thailand, from 2004 to 2010. Key information was retrieved from in-patient records, out patient cards, laboratory reports and registers. Patients were classified into three severity groups: nonsevere, severe (those with at least one organ involvement), and deceased. Prognostic characteristics for scrub typhus severity were analyzed by a multivariable ordinal continuation ratio regression. Results: A total of 526 patients were classified into nonsevere (n = 357), severe (n = 100), and deceased (n = 69). The significant multivariable prognostic characteristics for scrub typhus severity were increased body temperature (odds ratio [OR] = 0.58, 95% confidence interval [CI] = 0.45-0.74, P < 0.001), increased pulse rate (OR = 1.03, 95% CI = 1.01-1.05, P < 0.001), presence of crepitation (OR = 3.25, 95% CI = 1.52-6.96, P =0.001) increased percentage of lymphocytes (OR = 0.97, 95% CI = 0.95-0.98, P = 0.001), increased aspartate aminotransferase (every 10 IU/L) (OR = 1.04, 95% CI = 1.02-1.06, P=0.001), increased serum albumin (OR = 0.47, 95% CI = 0.27-0.80, P = 0.001), increased serum creatinine (OR = 1.83, 95% CI = 1.50-2.24, P < 0.01), and increased levels of positive urine albumin (OR = 1.43, 95% CI = 1.17-1.75, P< 0.001). Conclusion: Patients suspicious of scrub typhus with low body temperature, rapid pulse rate, presence of crepitation, low percentage of lymphocyte, low serum albumin, elevated aspartate aminotransferase, elevated serum creatinine, and positive urine albumin should be monitored closely for severity progression. © 2013 Sriwongpan etal.